Comparative codon usage pattern analysis of Eubacterium eligens, E. limosum and E. rectal - Shende, Kishor; Mishra, Anita; Gothalwal, Ragini; Iqbal, Mudasir (Recent Research in Science and Technology, 2013)
Analysis of codon usages data has both practical and theoretical importance in understanding the basics of molecular biology. Current study was aimed to study the codon usage preferences pattern and biases in three Eubacterium species viz. E. eligens, E. limosum and E. rectal. Eubacterium is the second most common genus after the genus Bacteroides in human intestinal tract, which are anaerobic, non-spore forming, and gram-positive rods. ORF sequence file were obtained from NCBI ftp site and analyzed by CodonW. E. eligens and E. rectal are AT-rich consisting of 62.04% and 57.82% AT-content. E. limosum has equal content of GC (48.62%) and AT (51.38%). In E. rectale and E. eligens showed maximum preferences for ‘A’ or ‘T’ ending codons whereas in E. limosum, ‘A’ or ‘T’ and ‘G’ or ‘C’ ending codons are preferred equally. In case of E. limosum the ‘GC’ drifts has influenced the codon usage pattern in this bacteria. All three Eubacterium sp. has shown low level codon usage heterogenesity among the genes. Nc-GC3 plot indicated major influence of compositional constraints in Eubacteria eligens and E. rectal. Beside E. rectal has additional factor influencing the codon usage. In E. limosum translational selection and additional factors are dominant over compositional constraints. The study indicates the close relationship between E. eligens and E. rectal and E. limosum diverging from them due to GC drift.